The calculations of P-T diagrams of Ni and Al using molecular dynamics simulation - Gurler, Y; Ozgen, S (Elsevier, 2003)
Theoretical determination of phase diagrams of metallic substances is very important in both technological and scientific point of views. The Gibbs free energy is widely used in the calculation of equilibrium phase diagrams. The free energy is not directly calculated in molecular dynamics (MD) simulations and it can be calculated by using harmonic and anharmonic approaches. In this study, molecular dynamics simulations are carried out using Finnis-Sinclair (FS) total energy expression based on many body interactions and P-T diagrams are determined for Ni and Al metallic systems. In addition, bulk modulus and linear thermal expansion coefficients are calculated in solid phases of the model systems. The obtained results were in agreement with literature. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: molecular dynamics simulation; embedded atom method; phase diagrams